NALAR ḤIKMAH DALAM FATWA DSN-MUI TENTANG PENGGUNAAN DANA TIDAK BOLEH DIAKUI SEBAGAI PENDAPATAN (TBDSP) BAGI LEMBAGA KEUANGAN SYARIAH - Achmad Nursobah; Muhajir (Jurnal Ilmiah Ekonomi Islam, 2025)
This study discusses the application of the theory of at-ta‘līl bil ḥikmah as the foundational basis in the formulation of DSN-MUI Fatwa No. 123/DSN-MUI/XI/2018 concerning Funds That Cannot Be Recognized as Income (TBDSP). Employing a normative qualitative method and an uṣūl al-fiqh approach grounded in at-ta‘līl bil ḥikmah, the study explores how ḥikmah (wisdom) serves as the primary rationale in legal determination, shifting away from the dominance of the traditional ‘illah-based reasoning. This theory emphasizes justice, utility, balance, ethics, and ease as integral dimensions in formulating legal rulings that are both relevant and adaptive. The findings demonstrate that the DSN-MUI fatwa on TBDSP not only fulfills the normative requirements of Islamic law but also provides contextual solutions that address the realities of the modern economic environment. By channeling non-halal funds toward social purposes, such as mosque construction and scholarships, the fatwa ensures legal protection, moral integrity, and public welfare. Consequently, the at-ta‘līl bil ḥikmah approach represents a vital methodological foundation for developing fatwas that are both responsive to contemporary changes and firmly rooted in Islamic legal principles.